Role of Digital Natives in Promoting Better Extension Services - ., Aditya; Sohane, RK (Journal of Agricultural Extension Management, 2018)
With the rapid explosion of social media content and availability of cheap devices, there is now no dearth of information available to more people from a greater number of sources than at any time in human history. As a result, basic human activities are constantly changing and new possibilities are rapidly emerging. Digital natives feel empowered with respect to learning opportunities because of their familiarity with and access to Information and Communication Technologies (ICTs). Some of the innovative tools will help digital natives to work for the larger community and provide extension services in a better way Bihar Agricultural University, Sabour is using various tools of social media like YouTube and innovative platforms like videoconferencing for better dissemination of information among the farmers and other stakeholders.